Polymer-clay nanocomposites thermal stability: experimental evidence of the radical trapping effect - Carvalho, Hudson W. P. [UNESP]; Santilli, Celso Valentim [UNESP]; Briois, Valerie; Pulcinelli, Sandra Helena [UNESP] (Royal Soc Chemistry, 2013)
The radical trapping flame retardant mechanism of polymer-clay nanocomposites is frequently claimed to be responsible for improving the thermal stability of polymers. However it had never been demonstrated. Herein using in situ time-resolved X-ray Absorption Spectroscopy (XAS) we present experimental evidence that Fe3+ embedded in the clay can act as electron acceptors during polymer thermal decomposition. Therefore it contributes to improve the polymer thermal stability.